Shoot and root interference of morning glory on the initial growth of sugarcane - Alves, Felipe C. [UNESP]; Bianco, Silvano [UNESP]; Nepomuceno, Mariluce P. [UNESP]; Martins, José Valcir F. [UNESP]; Alves, Pedro Luís da Costa Aguiar [UNESP] (FapUNIFESP (SciELO), 2018)
Among weeds, morning glories comprise a very important group of climbing plants that infest sugarcane crops. The objective of this study was to evaluate the shoot and root interference of Merremia cissoides on the initial growth of sugarcane cultivar RB 966928. The experiment consisted of five treatment groups: (i) sugarcane monocropping, (ii) morning glory monocropping, (iii) sugarcane intertwined with morning glory but inseparate boxes, (iv) sugarcane intertwined with morning glory in attached boxes and (v) sugarcane with morning glory in attached boxes with morning glory prevented from intertwining with the sugarcane. The experimental design consisted of randomized blocks with four replicates. Merremia cissoides adversely affected the initial growth of the RB 966928 sugarcane starting at 90 days after transplanting (DAT). This effect increased with the time of intercropping, reaching at 180 DAT with a reduction of 57.3% in height,15.5% in stalk diameter, 90.4% in leaf areas, 86.6 and 75.2% in stalk and leaf dry mass, respectively. These reductions primarily due to the weed intertwining with the sugarcane plants because the weed had a physical choking and shading effect. This negative effect of morning glory on the sugarcane plants increased when they shared the substrate (i.e., when they competed for space and water), which also adversely affected weed growth, reducing 50.2% leaf areas and 42.1% shoot dry mass. The leaf area and the stalk and leaf dry mass of sugarcane are the characteristics more sensitive to the weed interference. Thus, both the shoot and root of M. cissoides interferes negatively in the growth of sugarcane, with the effect proportional to the period of coexistence, highlighting the detrimental effect on the stem (greater economic interest), and may also compromise the mechanical harvesting of the crop.
Keywords: Competition; Merremia cissoides; Methodology; Saccharum